The Role of TLR2, TLR4, and TLR9 in the Pathogenesis of Atherosclerosis - Mohsin H. K. Roshan; Amos Tambo; Nikolai P. Pace (International Journal of Inflammation)
Toll-like receptors (TLRs) are key players in the pathogenesis of inflammatory conditions including coronary arterial disease (CAD). They are expressed by a variety of immune cells where they recognize pathogen-associated molecular patterns (PAMPs). TLRs recruit adaptor molecules, including myeloid differentiation primary response protein (MYD88) and TIRF-related adaptor protein (TRAM), to mediate activation of MAPKs and NF-kappa B pathways. They are associated with the development of CAD through various mechanisms. TLR4 is expressed in lipid-rich and atherosclerotic plaques. In TLR2−/− and TLR4−/− mice, atherosclerosis-associated inflammation was diminished. Moreover, TLR2 and TLR4 may induce expression of Wnt5a in advanced staged atheromatous plaque leading to activation of the inflammatory processes. TLR9 is activated by CpG motifs in nucleic acids and have been implicated in macrophage activation and the uptake of oxLDL from the circulation. Furthermore, TLR9 also stimulates interferon-α (INF-α) secretion and increases cytotoxic activity of CD4+ T-cells towards coronary artery tunica media smooth muscle cells. This review outlines the pathophysiological role of TLR2, TLR4, and TLR9 in atherosclerosis, focusing on evidence from animal models of the disease.